Innovative Integration and Optimization of RE and Smart Energy Management Systems in Skyscrapers: Enhancing Sustainability and Energy Self-Sufficiency in Vertical Cities - Yan Bingzhuo (E3S Web of Conferences)
Skyscrapers have become a vital part of modern urban development, offering efficient space utilization in increasingly dense cities. However, their huge input of energy as well as environmental impact necessitate integration of RE with intelligent energy management systems. This paper reviews key strategies for incorporating renewable energy (RE) technologies such as solar, wind, geothermal, and hybrid systems into skyscrapers. It also explores the role of Smart Energy Management Systems (SEMS) in optimizing energy use through real-time monitoring, predictive analytics, and automated control. Case studies like Masdar City and Shanghai Tower illustrate successful applications of these technologies. Despite challenges such as limited space, technological constraints, and high costs, emerging advancements in solid-state batteries, artificial intelligence, and Internet of Things (IoT)-based energy systems present significant opportunities. The review concludes that integrating RE and SEMS is critical for reducing the environmental impact of skyscrapers and creating more sustainable urban environments.